Spring circulation characteristics and formation mechanism in the Beibu Gulf - Gao, Jingsong; Mo, Lingqing; Lu, Hanfang; Meng, Xiaoni; Wu, Guidan; Wang, Dapeng; Nguyen, Kim-Cuong; Hu, Baoqing; Tran, Anh Tu (Frontiers in Marine Science, 2024)
Spring circulation in Beibu Gulf remains an underinvestigated research topic.Μodel results validated by observations reveal that the northern and southern parts of Beibu Gulf are controlled by an enclosed cyclonic gyre and a cyclonic gyre, respectively, while in the vertical, the circulation at the surface differs from those in the middle and deep layers.Contrary to that of the classical view, the modeled Qiongzhou Strait (QS) current flows eastward during some days in spring. This eastward current has an occurrence proportion of 29.3-55.4%, and its longest duration period is 7~18 d. The average current in the QS in spring is approximately westward except in some typical years. In spring, the northern Beibu Gulf is affected by the cold water mass (CWM), which is depicted by the 12 ℃ and 10 ℃ isolines in strong and weak years, respectively. Sensitivity experiments show that the heat flux is dominant in the northern Beibu Gulf via the effect of the CWM, and the monsoon wind favors the formation of the cyclonic gyre. Conversely, the cyclonic gyre in the southern Beibu Gulf is jointly driven by the monsoon wind and heat flux, with the effect of the monsoon wind being more significant. The current off the northern coast of Vietnam (VNC) can be either northeastward or southwestward in spring in different years. The VNC is mainly controlled by the elevation gradient along the northern coast of Vietnam, and the Coriolis force, horizontal advection, and vertical diffusion also play significant roles. Additionally, the CWM is mainly controlled by the heat flux whereas the monsoon wind plays a secondary role.